Relationship between Leadership, Motivation, and Public Services - Hartati, Tati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Public administration has a strategic value for administrators of government, development, and service to the community so that the need for effective, coordinated and sustainable public administration services. To achieve these objectives, a good motivation is needed from subdistrict head as the leader. The public administration service is apparently still not optimal. It happens because by the implementation of motivation has not been done optimally, based on the principles of motivation. This study used descriptive quantitative research methods with scoring techniques. The data collected was the primary data through questionnaire techniques and the secondary data through documentation and other supporting data. In this study, the samples were all employees in Argapura, Majalengka. The obtained results explained that the implementation of motivation by the sub-district head of Argapura based on the principles of motivation only reached the results of 61.5% which "Good Enough". Meanwhile, the effectiveness of public administration services obtained as much as 59% in which it only achieved "Good Enough". Thus, the motivation achieving a good enough predicate will influence the effectiveness of public administration services also achieving good enough results as well.